2005
DOI: 10.1681/asn.2004070568
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interactions between TGF-β1 Actions and the 12/15-Lipoxygenase Pathway in Mesangial Cells

Abstract: Diabetic nephropathy (DN) is characterized by mesangial cell (MC) hypertrophy and progressive accumulation of glomerular extracellular matrix (ECM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 50 publications
(68 reference statements)
5
61
0
Order By: Relevance
“…We previously reported that 12/15-LO and its products can increase TGF-␤1 expression and signaling in MC and vice versa. 17 Taken together with our present observations, it appears that 12/15-LO can crosstalk and amplify the effects of two key potent profibrotic and renal dysfunction-induced agents, TGF-␤1 and Ang II.…”
Section: ( S ) -H E T E 1 2 ( S ) -H E T E + a N G IIsupporting
confidence: 84%
See 4 more Smart Citations
“…We previously reported that 12/15-LO and its products can increase TGF-␤1 expression and signaling in MC and vice versa. 17 Taken together with our present observations, it appears that 12/15-LO can crosstalk and amplify the effects of two key potent profibrotic and renal dysfunction-induced agents, TGF-␤1 and Ang II.…”
Section: ( S ) -H E T E 1 2 ( S ) -H E T E + a N G IIsupporting
confidence: 84%
“…[17][18][19][20] Furthermore, cellular growth, matrix production, activation of oxidant stress, specific signaling pathways, and transcriptional factors were attenuated in MMC derived from 12/15-LOKO mice relative to wild type. 20 Importantly, the growth-promoting and matrixinducing effects of Ang II in MC were blocked by 12-LO inhibitors and were also attenuated in MMC derived from 12/15-LOKO mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations